Healthier side dishes at restaurants: an analysis of children's perspectives, menu content, and energy impacts. - Anzman-Frasca, Stephanie.; Dawes, Franciel.; Sliwa, Sarah.; Dolan, Peter R.; Nelson, Miriam E.; Washburn, Kyle.; Economos, Christina D. (2016)
Background: Children consume restaurant-prepared foods at high rates, suggesting that interventions and policies targeting consumption of these foods have the potential to improve diet quality and attenuate excess energy intake. One approach to encouraging healthier dietary intake in restaurants is to offer fruits and vegetables (FV) as side dishes, as opposed to traditional, energy-dense accompaniments like French fries. The aims of the current study were to examine: children's views about healthier side dishes at restaurants; current side dish offerings on children's menus at leading restaurants; and potential energy reductions when substituting FV side dishes in place of French fries.; Keywords: Restaurants, Children, Food away from home, Fruit, Vegetables, Side dishes, Defaults, Healthy eating, Childhood obesity.; Springer Open.